(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: The effect of socioeconomic inequity on major public health indices such as maternal and child mortality rates in low- and middle-income countries are less understood and needs to be evaluated through the concentration index. Method: This cross-sectional study was conducted in 2012 in Hamadan City, the west of Iran, and 1400 households were enrolled through a stratified cluster random sampling method. The effect of inequity on health outcomes was investigated via a three-stage procedure including: (a) definition of health outcomes; (b) measuring socioeconomic status using an asset index; and (c) measuring inequality of health outcome using concentration index (CI). Results: There was inequality for all outcomes of interest. The CI was negative for low birth weight, underweight, stunting, wasting, minor injuries, moderate injuries, consanguineous marriage, child with disability, short birth spacing, and adolescent pregnancy indicating the disproportionate concentration of the health outcomes among the poor. On the other hand, CI was positive for preterm birth, Nonexclusive breastfeeding, severe injuries, incomplete health care, cesarean section, and advanced maternal age indicating opposite conclusion. Conclusion: According to our results, there is a health inequality between the poor and the rich subgroups which may increase the risk of mothers and infant mortality and morbidity rates among the poor while the majority of the conditions related to the health outcomes are preventable.